A heuristic evaluation to support the instructional and enjoyment aspects of a math game. Issue 4 (7th November 2017) - Yeni, Sabiha; Cagiltay, Kursat
Abstract : Purpose: The purpose of this paper is to provide information about the design principles of educational games in the context of an educational math game example to educational game developers and instructors. Especially, it tries to demonstrate the importance of the academic content-fantasy integration and entertainment factors of educational games from the viewpoint of the experts. For this purpose, as a sample, an educational math game was examined to see how successful is the academic aspect, fantasy aspect, academic-fantasy aspects integration and enjoyment aspect of the game. Good aspects of the game and aspects need improvement were summarized for guidance to game developers while producing educational games. Design/methodology/approach: In this study, heuristic evaluation method was used for evaluating the educational math game. In the scope of this study, an example of modern educational computer game was examined by experts in this study. The integration of academic-fantasy context and enjoyment aspects of the game were analyzed deeply by using qualitative and quantitative data collection methods together. Findings: According to Relevance Embedding Translation Adaptation Immersion and Naturalization rubric results, embedding element received the highest mean score. It showed that the academic content is well coupled with the fantasy/story content. According to GameFlow criteria, clear goals and feedback sections got the highest scores; on the contrary immersion section got the lowest score. Immersion element of the game should be improved. According to the interview findings, more than half of the participants stated that, in terms of academic content of game, players can actively be involved in learning process during the game. The story of the game and elements used in the game have counterpart in daily life. Didactic elements do not affect learners' flow in the game. It is easy to learn and feedbacks are enough and useful. Originality/value: This study offered suggestions to designers for developing good educational games which are well balanced with academic and fantasy context.